2015
DOI: 10.5826/dpc.0504a04
|View full text |Cite
|
Sign up to set email alerts
|

Oral and written counseling is a useful instrument to improve short-term adherence to treatment in acne patients: a randomized controlled trial

Abstract: Background:Therapeutic success in acne patients not only depends on the appropriate selection of drugs but also on the patient’s treatment adherence or compliance. Lack of adherence is an important problem both in general medicine and in dermatologic practice.Objective:To evaluate the impact of oral and written counseling on treatment adherence among acne patients.Patients and Methods:Eighty patients were randomized into two groups of 40 patients each. The intervention group received a patient information leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For effective patient education and counselling on the treatment of chronic disease, various means of information such as reading materials, videos, and reminders may be utilized [ 21 – 23 ]. Recent studies have shown that written counselling significantly improved adherence in acne patients [ 24 ]. Moreover, evidence from an observational study has shown that A/BPO gel leads to good treatment adherence for the majority of patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For effective patient education and counselling on the treatment of chronic disease, various means of information such as reading materials, videos, and reminders may be utilized [ 21 – 23 ]. Recent studies have shown that written counselling significantly improved adherence in acne patients [ 24 ]. Moreover, evidence from an observational study has shown that A/BPO gel leads to good treatment adherence for the majority of patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non‐adherence to medicines is also a significant contributor to poor patient outcomes, with up to 15% of adverse drug events relating to non‐adherence . Patient counselling when starting new medicines has been shown to improve patient safety, medication adherence, and patient satisfaction . In addition to improving outcomes there is an ethical and legal requirement for patients to be informed about care .…”
Section: Introductionmentioning
confidence: 99%
“…Studies highlight specific deficiencies in the communication of medicine name, indication for use, how to take the medicine and adverse effects . These deficiencies can be improved with the use of written information for patients . Written medicines information is most effective when combined with verbal counselling and is less effective when used alone as a ‘handout’ …”
Section: Introductionmentioning
confidence: 99%